1998
DOI: 10.2307/176865
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Northern Red Oak: Positive and Negative Effects of Competitor Removal

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. The decreased ability of northern red oak (Quercus rubra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
76
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 8 publications
(14 reference statements)
2
76
0
2
Order By: Relevance
“…The acorns are consumed by insects, deer, and small mammals. Natural regeneration of NRO throughout its range in the eastern USA is difficult because of several factors, such as interspecific competition, predation, disturbance, and reproductive mode (Crow 1988;Steiner 1995;Buckley et al 1998). Acorn production is highly variable (3-to 5-y intervals) and populations of NRO do not produce acorns abundantly until they are 25 y of age (Olson 1974).…”
Section: Introductionmentioning
confidence: 99%
“…The acorns are consumed by insects, deer, and small mammals. Natural regeneration of NRO throughout its range in the eastern USA is difficult because of several factors, such as interspecific competition, predation, disturbance, and reproductive mode (Crow 1988;Steiner 1995;Buckley et al 1998). Acorn production is highly variable (3-to 5-y intervals) and populations of NRO do not produce acorns abundantly until they are 25 y of age (Olson 1974).…”
Section: Introductionmentioning
confidence: 99%
“…Both containerized seedlings and standard bare-root stock have been employed in post-harvest settings, but have proven unsuccessful in many cases (Hilt, 1977;Loftis, 1979;McGee and Loftis, 1986) due to competing forms of reproduction such as sprouting, especially when site productivity is high (Olson and Hooper, 1972;Russell, 1973). In addition, competition from non-native invasive (NNI) plants and herbivory from whitetail deer (Odocoileus virginianus (Boddaert)) have impeded artificial regeneration success (Gottschalk and Marquis, 1983;Gordon et al, 1995;Buckley et al, 1998;Oswalt et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Concomitantly, deer browsing has profoundly impacted both the composition and structure of many plant communities, including the depression of natural (Rooney and Waller, 2003) and artificial (Buckley et al, 1998) oak regeneration. In addition, deer herbivory can result in increased seedling mortality (Buckley et al, 1998) and significant impacts on height growth (Oswalt et al, 2004). The aggregate effect is the reduced competitive capacity of planted oak seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…Growing-season precipitation and atmospheric temperature, and soil properties were similar at all stand locations in 1991 and 1992 (Kim et al 1996;Buckley et al 1998). …”
Section: Study Sitesmentioning
confidence: 86%
“…Changes in soil nutrient and light availability caused by canopy removal could affect nutrient-use efficiency and nutrient uptake of growing vegetation (Covelo and Gallardo 2002). Although several studies have reported on the dynamics of biomass and nutrient distribution of understory vegetation after clearcutting (Ohmann and Grigal 1979;Reiners 1992), information is also needed on how understory vegetation responds to varying degrees of canopy cover because of the increasing use of partial canopy manipulations in forest regeneration (Kim et al 1996;Buckley et al 1998). In this study, we investigated the effects of canopy cover changes on leaf mass, N and P levels in understory vegetation in northern red oak and red pine stands.…”
Section: Introductionmentioning
confidence: 99%